Mathematical creative thinking ability: The impact of adversity quotient on triangle and quadrilateral shapes material - Rizalno, Slamet Mey; Purwanto, Sigid Edy (Desimal: Jurnal Matematika, 2022)
This research has a background, namely the ability to think mathematical creatively. This is because students pay less attention to the mathematics learning process. This will have an impact on the ability to think creatively in mathematics so that it will not develop properly. Adversity Quotient is the creative thinking ability of a student who can solve problems well if supported by good solving skills. The purpose of this research is to see the creative thinking ability of students in terms of the adversity quotient. The method in this research is descriptive qualitative research with an interview process. Data collection in this research is in the form of instrument questions that contain indicators of creative thinking, namely fluency, flexibility, originality, and elaboration. The results of the research were seen from the results of the answers to the questions on the mathematical creative thinking ability instrument and the adversity quotient, which contained that students had three types of adversity quotient, namely Climbers, Campers, and Quitters. Subjects with indicators of fluency, flexibility, originality, and elaboration with the Climbers type were able to solve the questions according to each indicator, the Campers type students were able to solve the questions correctly but were still lacking in preparing answers, and the Quitters type students still did not understand how to solve the questions so that the answer was wrong.